What steps do we need to take to improve diagnosis of tuberculosis in children?. Issue 7 (July 2015) - Venturini, Elisabetta; Remaschi, Giulia; Berti, Elettra; Montagnani, Carlotta; Galli, Luisa; de Martino, Maurizio; Chiappini, Elena
<x xml:space="preserve">Abstract</x> Tuberculosis still represents a big global public health challenge. The diagnosis of tuberculosis and the differentiation between active and latent tuberculosis remain difficult, particularly in childhood, because of the lack of a gold standard test for diagnosis. In the last decade, novel diagnostic assays have been developed. Among immunologic tests, new assays based on the measurement of different cytokines released by specific T cells in response to Mycobacterium tuberculosis antigens, other than INF-γ, have been investigated. Promising results rely on nucleic acid amplification techniques, also able to detect drugs resistance. Innovative research fields studied the modifications of CD27 expression in T cells as well as different host gene expression in response to M. tuberculosis. Further studies are needed to assess the diagnostic value and the accuracy of these new assays.